Geośrodowiskowe uwarunkowania lokalizacji przemysłu wydobywczego w gminie Brody i Gubin = Geo-environmental analysis of the conditions for the location of the open pit mine in the Gubin-Brody commune - Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an analysis of geo-environmental conditions for the location of the mining industry in the communities of Gubin and Brody. Described area is located in western Poland (lubuskie province) and characterized by a plain relief (relative height differences aprox. 12 m), diversity of bed rock (sands of various origins, clays), a relatively large variability of weather conditions, especially the annual rainfall (484-746 mm in 2005-2011), the presence of underground aquifers and many forms of surface waters and diversity of soil cover. The dominant form of land use is forest and arable land. Municipalities are rich in wildlife protected areas. Directly on the planned investment area is located (in a part) Natura 2000 "Lake Brodzkie" area.
Keywords: uwarunkowania lokalizacji; warunki środowiskowe; environmental conditions of the location